1996
DOI: 10.1007/bf02658498
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of elastin and aorta with sugars in vitro and their effects on biochemical and physical properties

Abstract: Stiffening of blood vessel walls occurs in the early stages of atherosclerosis, and this process is known to occur earlier in diabetic subjects. The effect could be due, in part, to glycation. Although collagen is responsible for ensuring the ultimate tensile strength of the tissue, elastin largely determines the compliance of the vessel wall in the normal physiological range of pressures and this appears to be closely matched to haemodynamic requirements. Changes in elastin are therefore likely to affect opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 24 publications
1
68
0
7
Order By: Relevance
“…[22][23][24][25] In fact, in vitro and animal models of diabetes mellitus and hyperglycemia have shown that AGEs cross-linking with elastin and collagen increases the slop of force-extension curve significantly, and that arterial stiffness is closely correlated with arterial content of pentosidine. 9,10 Our findings show a significant association between serum pentosidine levels and progression of aortic stiffness, suggesting that AGEs could play a significant role in the progressive aortic stiffness in this population.…”
Section: Discussionmentioning
confidence: 64%
“…[22][23][24][25] In fact, in vitro and animal models of diabetes mellitus and hyperglycemia have shown that AGEs cross-linking with elastin and collagen increases the slop of force-extension curve significantly, and that arterial stiffness is closely correlated with arterial content of pentosidine. 9,10 Our findings show a significant association between serum pentosidine levels and progression of aortic stiffness, suggesting that AGEs could play a significant role in the progressive aortic stiffness in this population.…”
Section: Discussionmentioning
confidence: 64%
“…It is well known that the level of reactants used to study the effects of glycation on connective tissue proteins (i.e. 100-250 mM) are well above those encountered in vivo (Kohn et al, 1984;Fu et al, 1994;Winlove et al, 1996). The rationale behind the use of supraphysiologic reactant concentrations is to identify the end-products of the reaction and to simulate functional, biomechanical, and biochemical changes that could take decades to develop in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-linking of elastin is through the same lysine-based reactions as those of collagen, but differ in that the cross-linking of elastin chains is much more extensive. Elastin can also undergo age-related stiffening as a consequence of production of AGEs [22].…”
Section: Elastinmentioning
confidence: 99%